Answer:
a = -3, b = 1
Explanation:
1. Plug in the given values into the equations:
a(-1) - b(2) = 1
a(2) + b(-1) = -7
2. Isolate a in the first equation:
a(-1) - b(2) = 1 = a · -1 - b · 2 = 1
-a - 2b = 1
-a -2b+2b = 1+2b
-a = 1 + 2b
![(-a)/(-1) =(1)/(-1) +(2b)/(-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/lnj01d3uzl69hfdohmqj231djgukaesctm.png)
a = -1 - 2b
3. Substitute "a = -1 - 2b" in for a in the second equation:
(-1 - 2b)2 + b(-1) = -7
4. Simplify:
-2 - 4b + b(-1) = -7
-2 - 4b -b = -7
-2 -5b = -7
5. Isolate for b:
-2+2 - 5b = -7+2
-5b = -5
![(-5b)/(-5) =(-5)/(-5)](https://img.qammunity.org/2023/formulas/mathematics/high-school/f8kmsoefe2cqkxnx62tsdx0vx4wl5klsxo.png)
b = 1
6. Substitute the b value into an equation to solve for a:
a = -1 -2 · 1
a = -3 · 1
a = -3
hope this helps!